2015
DOI: 10.1016/j.mri.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Towards the identification of multi-parametric quantitative MRI biomarkers in lupus nephritis

Abstract: Keywords:Renal function Multi-parametric quantitative MRI (qMRI) Arterial spin labeling (ASL) Blood oxygen level dependent (BOLD) T1rho MRI Lupus nephritis (LN) Purpose: To identify potential biomarkers of the renal impairment in lupus nephritis using a multi-parametric renal quantitative MRI (qMRI) protocol including diffusion weighted imaging (DWI), blood oxygen level dependent (BOLD), arterial spin labeling (ASL) and T1rho MRI between a cohort of healthy volunteers and lupus nephritis (LN) patients. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
3
39
1
Order By: Relevance
“…One study, published by Rapacchi et al in 2015, evaluated 10 LN patients and 10 matched healthy volunteers. In this study, the ADC values determined by DWI-MRI were not significantly different between the LN and control groups [12]. Another study by , which recruited 65 LN patients and 16 healthy volunteers, found a negative correlation between the mean ADC values and renal pathology chronicity indices [13].…”
Section: Introductioncontrasting
confidence: 42%
“…One study, published by Rapacchi et al in 2015, evaluated 10 LN patients and 10 matched healthy volunteers. In this study, the ADC values determined by DWI-MRI were not significantly different between the LN and control groups [12]. Another study by , which recruited 65 LN patients and 16 healthy volunteers, found a negative correlation between the mean ADC values and renal pathology chronicity indices [13].…”
Section: Introductioncontrasting
confidence: 42%
“…Further studies are needed to determine if early treatment with MMF in these patients may be beneficial to prevent TID. Novel approaches including molecular imaging, cell distance mapping, functional magnetic resonance imaging, as well as integrative biology approaches are being developed to identify early inflammatory changes, biomarkers and response to treatment in lupus nephritis [5255]. …”
Section: Discussionmentioning
confidence: 99%
“…ASL-derived estimates of cortical perfusion also correlate with CKD stage and the estimated glomerular filtration rate (eGFR) in patients with diabetic nephropathy (34). Similarly, ASL-derived estimates of renal blood flow are statistically different between patients with lupus nephritis and controls (35). ASL is particularly well suited to assess renal transplants because of the common superficial location of renal allografts in the pelvis.…”
Section: Clinical Applicationsmentioning
confidence: 99%